2019
DOI: 10.1063/1.5049837
|View full text |Cite
|
Sign up to set email alerts
|

Increased energy efficiency spin-torque switching of magnetic tunnel junction devices with a higher order perpendicular magnetic anisotropy

Abstract: Stéphane Mangin. Increased energy efficiency spin-torque switching of magnetic tunnel junction devices with a higher order perpendicular magnetic anisotropy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…[19] To minimize the power consumption, it has been shown that it is possible to achieve low power consumption using spin-transfer torque-based devices. [20][21][22][23][24] Several schemes have been proposed for mimicking the synapse, which acts as a memory for the neuron. This article presents the latest developments in multistate memory for NC.…”
Section: Introductionmentioning
confidence: 99%
“…[19] To minimize the power consumption, it has been shown that it is possible to achieve low power consumption using spin-transfer torque-based devices. [20][21][22][23][24] Several schemes have been proposed for mimicking the synapse, which acts as a memory for the neuron. This article presents the latest developments in multistate memory for NC.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Therein, a tunnel magnetoresistance (TMR) effect depends greatly on the thickness, topological properties of the free, pinned, barrier MTJ layers and/or the mean free path (MFP) of the electrons injected through those layers of an MTJ device. [10][11][12][13][14][15] In principle, majority carrier electrons with a long MFP can travel through a MTJ stack with low resistance (R ↑↑ ) when an external magnetic field aligns parallel to both magnetizations of the two ferromagnetic (FM) layers, whereas a higher resistance (R ↑↓ ) is observed if those FM magnetizations are opposite. 1,[3][4][5][6] Theoretical results showed that TMR ≈ 1100%, typically defined as (R ↑↓ −R ↑↑ )/R ↑↑ ), for a fully epitaxial MgO-MTJ could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…TMR ratio largely reduces at high annealing temperatures, effects of diffusion, migration and texture, are simultaneously included. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Despite the extensive research effort in MgO-MTJ structures, a better understanding on each MTJ and its fabrication processes at the microscopic level is indispensable. Therein, the transport properties of MTJs are largely dictated by their underlying microstructures, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin transfer torque random access memory (STT-MRAM) is a next-generation non-volatile memory technology [1][2][3][4] that has the advantage of fast write times [5][6][7] , relatively low power consumption [8][9][10][11] , and shows promise of scalability down to at least 7 nm CMOS technology node 12,13 . STT-MRAM has already found its applications in the form of stand-alone nonvolatile memory 14 , and efforts to realize embedded versions of STT-MRAM are under way 15,16 .…”
mentioning
confidence: 99%